Linguistic Errors and Skill-Competency of Students in Writing Business Letters - Joemar Antonio; Melvi Briones (Journal of English Education and Linguistics, 2022)
Business writing has a standard way of writing and formality in communication, this space for clearer and concise communication should be evident in the letter, otherwise, it shall create miscommunication and confusion. Thus, a level of students’ learning in terms of the knowledge of format and content should be mastered by the learners. Having this idea, the researcher pursued this study on the evaluation of the students’ business writing skills to help the students be prepared of future communication with the companies and be able to increase their confidence level in their written communication by avoiding technical and grammatical error. The study analyzed the Linguistics Errors and Skill-Competency in Business Letter Writing of student-leaders in College of Education in University of Nueva Caceres. This study sought identify kind of letters archived in the College of Education; determine the Linguistics Errors of College of Education students in Business Writing in terms of Mechanical, Morphological, Lexical, and Syntactic; recognize the Level of Competency in Business Writing Skills of College of Education students in terms of Format, and Content; establish the relationship of the Linguistic Error and the Level of Competency in Business Writing Skills of the College of Education students; and present an innovative instructional material may be produced by the researcher based on the result of the study. This study allowed the researcher to see that the Letter request is the common letters submitted in the office; that the students, despite their perception of being competent and highly competent in their business letter writing skills, are still committing errors particularly in the Punctuations, Sentence Structures, and Word Choice. Thus, should learn and relearn the important concepts in the business letter writing format and content. Lastly, should urge the future researchers to evaluate the innovative material done by the researcher so that it would be practically useful for the present and future student-leaders.